Hydromedusae composition, occurrence, and distribution in the Caeté river estuary, Pará - Mesquita, Silvana do Socorro Araújo; Costa, Rauquírio Marinho; Pereira, Luci Cajueiro Carneiro; Magalhães, André (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Species composition and spatio-temporal variation in density of hydromedusae along a salinity gradient were investigated in the Caeté river estuary, northern Brazil in June and December, 1998 (dry season) and in February and May, 1999 (rainy season). The Caeté river estuary was characterized by high spatial and temporal variations in salinity. Twelve taxa were recorded of which Octocanna haeckeli represent to new record for coastal waters of the northeast coast of Pará state. In general, the highest and lowest densities were found in December and May, respectively. This observation was probably due to differences in the rainfall rates between the two studied periods
Keywords: Hydromedusae; Spatial and temporal distribution; Estuary of Caeté river; Bragança; Pará